ANALYSIS OF PROGRAMMING EDUCATION AT THE PRIMARY EDUCATION LEVEL - Saimassay, Gulnara (Journal of Emerging Technologies and Computing, 2024)
Programming education has traditionally been provided at the undergraduate level worldwide. However, in recent years, there has been a growing trend in developed countries to introduce programming education at earlier ages with the aim of promoting software literacy, improving programming skills, and making programming education accessible to a wider audience. While some countries are updating their informatics lessons to include programming, others are incorporating programming lessons into their primary education curriculum for the first time. The level at which programming training is offered also differs between countries. The objective of this research is to explore how countries have integrated programming education into their curricula and to identify the differences between countries in terms of programming education. The study aims to answer the question of how programming education is provided at the primary education level both domestically and abroad. The research has found that programming education is increasingly recognized as important and many countries are now allowing programming lessons in their education curriculum, with some countries even introducing programming education in kindergarten. However, there are variations in the programming languages used and the skills taught to students across different countries.